Modern pollen–vegetation relationships in north-central Oman and their implications for interpreting fossil pollen records from extremely arid environments - Julia Unkelbach; Lucas Proctor; Hermann Behling (Palynology, 2026)

Population Genomics of a Cosmopolitan Weed Provides Insights Into Its Local Adaptation and Recent Demographic History - Marilia Souza Lucas; Christoph Rosche; Isabell Hensen; Stefan G. Michalski; Dávid U. Nagy; Diana Gamba; Renske E. Onstein; Karime Abidkulova; Mohammad Al‐Gharaibeh; Ali A. Al‐Namazi; Sirwan Babaei; Fernando Bastida; et al. (Molecular Ecology, 2026)
Invasive plant species present a growing ecological and economic challenge, and often adapt rapidly to their novel environments through complex demographic and evolutionary processes. Invasion genomics offers powerful tools to disentangle these processes, but most studies rely on geographically narrow sampling across native and non‐native ranges. Erigeron canadensis is a cosmopolitan weed native to North America that has successfully invaded diverse climates worldwide. We used double‐digest restriction site‐associated DNA sequencing (ddRADseq) to investigate the genetic diversity and structure of 280 E. canadensis populations across the Northern Hemisphere. We found that native and non‐native populations maintained comparable genetic diversity. Population structure analyses revealed four genetic clusters that were mainly differentiated along latitudinal and aridity gradients. However, one cluster was strongly overrepresented in the non‐native compared to the native range. In the native range, genetic differentiation was shaped by spatial and environmental gradients, while in non‐native regions human‐mediated dispersal and repeated introductions disrupted environmentally driven genetic structure. Migration network analyses revealed limited intercontinental connectivity and a possible role of long‐distance dispersal in within‐range expansions. Genomic offset analyses showed that genotype‐environment mismatches in non‐native populations associated with reduced growth and reproduction. Together, our results indicate that the invasion dynamics of E. canadensis were driven by multiple introductions, population admixture, and lineage sorting, while some genotypes contributed disproportionately to the spread of this invader. The presence of apparent maladaptation suggests that even long‐established invaders may still be evolving in response to their novel environment, raising concerns about potential future expansions.

Melanoides tuberculata and Zootecus insularis gastropod shells provide a snapshot into past hydroclimatic conditions of arid environments: New perspectives from Oman - Katharina E. Schmitt; Tara Beuzen-Waller; Conrad Schmidt; Lucas Proctor; Susanne Lindauer; Christoph J. Gey; Dana Pietsch; Bernd R. Schöne (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Examining long-term fuel and land use patterns at Ziyaret Tepe, Türkiye using an integrated analysis of seeds, wood charcoal, and dung spherulites - Lucas Proctor; Alexia Smith; Timothy Matney (Archaeological and Anthropological Sciences, 2024)
This study presents the results of a combined dendrological, macrobotanical, and dung spherulite analysis of flotation samples collected from Bronze Age, Late Assyrian, and post-Assyrian contexts at the site of Ziyaret Tepe, located on the southern bank of the Tigris River in southeastern Anatolia. The results of this study show shifting fuel resource exploitation between pre-urbanized phases of the site (ca. 3000–1600 BCE), the urbanized Late Assyrian occupation (882–611 BCE), and the ruralized post-Assyrian (ca. 611 BCE–1500 CE) re-occupations of the site. During the Late Assyrian period, Ziyaret Tepe is thought to have been the location of the city of Tušhan, an important provincial capital of the Neo-Assyrian empire. Evidence for local deforestation near the Tigris River and expanding reliance on dung fuel use during this period indicate overexploitation of fuel resources as larger populations and extractive imperial economic policies placed heavier pressure on local land use. Qualitative dendrological data provides evidence for the intensification of fuelwood harvesting during this period, while textual evidence documented an expansive program of timbering to the north of the site intended to fuel imperial construction projects in the Assyrian heartland. Following the abandonment of Tušhan and the collapse of the Neo-Assyrian empire, local fuel resource exploitation during subsequent occupations of the site shifted towards the direct management of wood fuel resources and increasing reliance on rural pastoralism.

The burning issue of dung in archaeobotanical samples: a case-study integrating macro-botanical remains, dung spherulites, and phytoliths to assess sample origin and fuel use at Tell Zeidan, Syria - Alexia Smith; Lucas Proctor; Thomas C. Hart; Gil J. Stein (Vegetation History and Archaeobotany, 2019)